Molecular dynamics simulation of an entire cell - Stevens, Jan A.; Grünewald, Fabian; van Tilburg, P. A. Marco; König, Melanie; Gilbert, Benjamin R.; Brier, Troy A.; Thornburg, Zane R.; Luthey-Schulten, Zaida; Marrink, Siewert J. (Frontiers in Chemistry, 2023)
The ultimate microscope, directed at a cell, would reveal the dynamics of all the cell’s components with atomic resolution. In contrast to their real-world counterparts, computational microscopes are currently on the brink of meeting this challenge. In this perspective, we show how an integrative approach can be employed to model an entire cell, the minimal cell, JCVI-syn3A, at full complexity. This step opens the way to interrogate the cell’s spatio-temporal evolution with molecular dynamics simulations, an approach that can be extended to other cell types in the near future.